Human-de-centred Design – Towards a (new) era of suffering - Niccolò Casiddu; Francesco Burlando; Boyu Chen (Agathón)
To tackle the global challenges of the Anthropocene, this paper proposes the concept of Human-de-centred Design, a new design approach aimed at decisively moving beyond Human-centred Design. Positioned as a stronger alternative to similar attempts from the posthumanism field, this new paradigm promotes a vision in which the needs of ‘non-human agents’ are prioritised. This leads to a proactive removal of the user from the centre of the design process, requiring that human interests be subordinated to the ecosystem’s needs. To achieve this post-anthropocentric revolution, the concept of the ‘era of suffering’ is introduced, intended to highlight the efforts required from humanity. To illustrate this concept, three case studies are analysed, demonstrating how design can challenge traditional logic and adopt a more radical perspective that removes the human user from the centre of the project.